2015
DOI: 10.1098/rspb.2015.0977
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for specificity in symbiont-conferred protection against parasitoids

Abstract: Many insects harbour facultative symbiotic bacteria, some of which have been shown to provide resistance against natural enemies. One of the best-known protective symbionts is Hamiltonella defensa, which in pea aphid (Acyrthosiphon pisum) confers resistance against attack by parasitoid wasps in the genus Aphidius (Braconidae). We asked (i) whether this symbiont also confers protection against a phylogenetically distant group of parasitoids (Aphelinidae) and (ii) whether there are consistent differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(139 citation statements)
references
References 66 publications
(105 reference statements)
1
137
1
Order By: Relevance
“…As seen in prior studies using H. defensa carrying different APSE variants, including APSE8, single infection with the present study's strain of H. defensa with APSE8 did not confer any protection against attack by the parasitoid P. pequodorum ( Fig. 3) (LRT, F H ϭ 0.011 and P ϭ 0.9155 [36]). …”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…As seen in prior studies using H. defensa carrying different APSE variants, including APSE8, single infection with the present study's strain of H. defensa with APSE8 did not confer any protection against attack by the parasitoid P. pequodorum ( Fig. 3) (LRT, F H ϭ 0.011 and P ϭ 0.9155 [36]). …”
Section: Resultsmentioning
confidence: 48%
“…Indeed, in a separate study which controlled for aphid genotypic effects, we found no evidence that X-type rescued loss of H. defensa-based protection at high temperatures, nor did we find that X-type provided any protection against the wasp A. ervi as a single infection (33). However, several studies with aphids, including pea aphids, show that symbiont-based protection against parasitoids can be specialized to particular parasitoid species (34)(35)(36)(37), rendering it possible that X-type provides protection specifically against the only other parasitoid, Praon pequodorum, commonly attacking the pea aphid in North America (38). In European pea aphids, some X-type strains have been implicated in providing protection from thermal stress, as well as challenges by the wasp A. ervi and the fungal pathogen P. neoaphidis (39).…”
mentioning
confidence: 99%
“…It has been shown that the resistance requires the presence of a bacteriophage (Oliver et al, 2009) that carries genes for putative eukaryote toxins which are presumed to act against the developing parasitoid (Degnan & Moran, 2008a, 2008b. Hamiltonella defensa strains vary considerably in the protection they provide , and there is evidence of both parasitoid-species and parasitoid-genotype specificity (Rouchet & Vorburger, 2012;Asplen et al, 2014;McLean & Godfray, 2015). A recent population cage experiment using a model aphid-parasitoid food web demonstrated that the presence or absence of H. defensa in one of the aphid species can affect community stability and dynamics (Rothacher et al, 2016;Sanders et al, 2016).…”
Section: Parasitoidsmentioning
confidence: 99%
“…Also, H. defensa-conferred resistance varies according to parasitoid species. (Mclean and Godfray, 2015). Finally, environmental factors such as heat may reduce the parasitoid resistance conferred by H.…”
Section: Hamiltonella Defensamentioning
confidence: 99%
“…The interrelation study between these factors become more prevalent in recent years, such as host plant, parasitoid and symbiont (Mclean and Godfray, 2015); aphid, host plant and symbiont (Peccoud et al, 2015;Zytynska et al, 2016); host plant, parasitoid, natural enemies, symbiont and environment (Smith et al, 2015). First, as described above regarding Arsenophonus, facultative symbionts may influence the adaptation and distribution of their hosts through the colonization of new plants and climatic regions (Henry et al, 2013).…”
Section: Symbionts Interactions With Biotic and Abiotic Environmentmentioning
confidence: 99%